Conveying the adaptation of management panaceas: The case of management gurus - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 2015)
In this chapter we examine how management gurus through the telling of epiphanic and non-epiphanic stories convey the level of adaptability of their ideas. We argue that for their ideas to leave the auditorium with the audience members they have to present them in ways which convincingly demonstrate that they are potentially pertinent to the variety of working lives of those who attend. Drawing on a Conversation Analytic approach, the chapter shows that in the post-story assessment the gurus use a double structure of humor then seriousness. The contrast between the light-heartedness of the story and the seriousness of the post-story conclusion provides emphasis to the message being delivered as well as the transition from the specifics of the story to the general applicability of the ideas being conveyed. Overall, the chapter argues that these stories provide attention and emphasis to central messages within these talks and thereby supply the underpinning conditions necessary for gurus’ ideas to flow beyond the venue of their talks.